Synthesis and Evaluation of Antimitotic Activity of N-Phenyl Tetralones - Umesha Basavaiah, Sowbhagya, Vinaya, Yeriyur Basavaiah Basavaraju (Journal of Applied Pharmaceutical Science, 2018)
Objectives: The presence of the methylenedioxy ring, substituents at ring C and no methoxy groups on ring D are responsible for the antimitotic property. The series of new N-phenyl tetralones have been synthesized, characterized and tested for their antimitotic activity. Methods: The structures of the title compounds were confirmed by infrared spectroscopy (IR), nuclear magnetic resonance (NMR) and mass spectroscopy methods. The synthesized compounds were tested for their antimitotic activity. Results: New N-phenyl tetralones were synthesized by chalcone method followed by copper oxide and potassium carbonate catalyzed aromatic nucleophilic substitution reaction and acid-mediated cyclization. They were screened for their antimitotic activity by onion root tip method. All the newly synthesized analogues exhibit moderate to good antimitotic activity. Among the synthesized analogues, compound 5e and 5f bearing electron donating methoxy group at para and 3,4,5- positions of the phenyl moiety showed predominant antimitotic activity. Conclusion: A series of new N-phenyl tetralones were synthesized in good yields by chalcone route method. This route attracts the attention because of its simple operating conditions and easy availability of chemicals. The synthesized compounds were screened for their antimitotic activity.
Keywords: 5-Acetyl-6-amino-1,3- benzodioxole, Chalcones, aldehydes, Onion root tip method, Antimitotic activity.